2020
DOI: 10.29313/mediator.v13i1.5782
|View full text |Cite
|
Sign up to set email alerts
|

Successful Social Media Advertising Activities For Micro, Small And Medium Enterprises

Abstract: In Indonesia, MSMEs are a business group that is a mainstay of economic activity that is able to support most of its citizens. Economic development in Indonesia depends on the development and improvement of the capacity of MSMEs. MSMEs will be helped by improving their marketing performance through social media advertising. The use of social media advertising will create easy, cheap and fast access. Social media advertising can be used by companies to distribute advertisements and create awareness for customer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Our data showed that 1,24% of the respondents used social media for their business. Some research also suggested that social media can be used as an advertising platform for Micro, Small and Medium Enterprises (Suryono et al, 2020) and macro businesses as well (Manurung et al, 2020). Additionally, we can conclude that they like the social media platform because it provides them with features that help them express their feelings and emotions more.…”
Section: Discussionmentioning
confidence: 78%
“…Our data showed that 1,24% of the respondents used social media for their business. Some research also suggested that social media can be used as an advertising platform for Micro, Small and Medium Enterprises (Suryono et al, 2020) and macro businesses as well (Manurung et al, 2020). Additionally, we can conclude that they like the social media platform because it provides them with features that help them express their feelings and emotions more.…”
Section: Discussionmentioning
confidence: 78%
“…The fact that currently, prospective students are active users of social media should be utilized as an opportunity for public relations practitioners to optimize the existence of that social media. Optimal use of social media can provide its advantages, such as easy access that is fast and cheap (Suryono et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Tuckwell (2007) calls it digital (interactive) communication, while Smith & Zook (2011) calls it a website and social media. The importance of using this element in helping to market MSME products is also widely mentioned in research (Ali Abbasi, Abdul Rahim, Wu, Iranmanesh, & Keong, 2022;Kolbe, Calderón, & Frasquet, 2021;Sinha & Fukey, 2021;Suryono, Rahayu, Astuti, & Widarwati, 2020). In Febriyantoro & Arisandi's research (2018), it is stated how digital marketing can make it easier for MSMEs to convey information and interact directly with consumers, expand market share, increase awareness, and increase sales (Febriyantoro & Arisandi, 2018).…”
Section: Discussionmentioning
confidence: 99%